Merit, Demons, and Karma: Catholic Victim Souls and the Tibetan Practice of gCod - Cattoi, Thomas (Buddhist Christian studies, 2022)
The purpose of this article is to map the points of contact, as well as the irreducible differences, between the Catholic tradition of victim soul spirituality and the Tibetan practice of gcod (chod). Victim soul spirituality develops in the framework of an Anselmian theology of the atonement, where the individual practitioner offers herself as an expiatory victim to God's wrath so to appease God's justice that requires reparation for the sins of humanity. A practice that knew its heyday in the Counter-Reformation period and enjoyed its highest degree of popularity in the late nineteenth and early twentieth century, victim soul spirituality, has virtually disappeared from contemporary Catholicism in the wake of the Second Vatican Council. At the same time, many Western practitioners of Buddhism have grown more interested in the practice of gcod (chod), which consists of a symbolic offer of one's body to demons and other malevolent beings that seek to thwart one's progress toward nirvāna. Developed originally by the female mystic Machig Labdron (1055-1149), gcod is analogous to victim soul spirituality as it reflects a sacrificial dialectic where individual practitioners can appease supernatural entities that can sustain or thwart our spiritual progress. At the same time, a close analysis of the two practices will reveal significant points of divergence, as the two traditions rest on radically distinct claims concerning individual subjectivity, soteriology, and the nature of ultimate reality.